PENERAPAN PEMBELAJARAN DENGAN MODEL STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) DALAM MENINGKATKAN SKILL SPEAKING SISWAKELAS XI IPS DI MA AL-BAIRUNY - rizki novia (JoEMS (Journal of Education and Management Studies), 2019)
This study aims to determine the application of learning with the STAD (Student Teams Achievement Division) model in improving students speaking skills. The method that used in this research is using quantitative methods with descriptive analysis. The subjects of this study is students of class XI IPS at Madrasah Aliyah Al-BairunySambongdukuhJombang. The data analysis technique used in this research is descriptive analysis. This study produces data that the application of learning with the STAD (Students Teams Achievement Division) model can improve students speaking skills with an average value 80.